2007
DOI: 10.1016/j.jcrs.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac tromethamine LS 0.4% versus nepafenac 0.1% in patients having cataract surgery

Abstract: Ketorolac tromethamine was statistically significantly better than nepafenac in terms of patient satisfaction, compliance, and postoperative pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…When amfenac was added to both cell lines, a statistically significant reduction in proliferation was observed, supporting the hypothesis that a COX-2 inhibitor can control the malignancy of certain types of tumors [21,22]. In recent years, numerous studies have been conducted in humans to analyze the safety and efficacy of nepafenac and to better understand the ability of topical NSAIDs to reach various tissues in the eye [3,8,10,11,[23][24][25][26][27]. NSAIDs are often used both before and after cataract surgery.…”
Section: Animal Studiesmentioning
confidence: 55%
See 2 more Smart Citations
“…When amfenac was added to both cell lines, a statistically significant reduction in proliferation was observed, supporting the hypothesis that a COX-2 inhibitor can control the malignancy of certain types of tumors [21,22]. In recent years, numerous studies have been conducted in humans to analyze the safety and efficacy of nepafenac and to better understand the ability of topical NSAIDs to reach various tissues in the eye [3,8,10,11,[23][24][25][26][27]. NSAIDs are often used both before and after cataract surgery.…”
Section: Animal Studiesmentioning
confidence: 55%
“…A higher incidence of posterior capsule opacification was reported in the nepafenac group. Statistically, ketorolac was slightly better in terms of patient compliance, satisfaction and postoperative pain control [25].…”
Section: Animal Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, nepafenac is described more, less, or equally effective to ketorolac. 67,[80][81][82] In their review, Faktorovich and Melwani found 23 prospective and randomized studies that included NSAIDs, anesthetics, opiates, acetaminophen, gabapentin, and pregabalin for pain control after PRK surgery. They concluded that although the efficacy of drugs prone to be similar, tetracaine (1%) and nepafenac (0.1%) tended to have the most analgesic effect showing the lowest P-values when compared with placebo.…”
Section: Acute Pain Managementmentioning
confidence: 99%
“…64 Nepafenac: Recent prospective randomized double-masked trials found nepafenac (0.1%) has satisfactory analgesic properties. [81][82][83] A randomized, double-masked, clinical trial, showed that nepafenac (0.03% and 0.1%) were effective for treatment of pain and photophobia in patients undergoing PRK surgery. 84 However, this drug is not approved yet by the FDA for treatment of postrefractive surgery pain.…”
Section: Acute Pain Managementmentioning
confidence: 99%